A historical review of the taxonomy and classification of Entocytheridae (Crustacea: Ostracoda: Podocopida) - Williams, Bronwyn W.; Weaver, Patricia G. (Zootaxa, 2018)
Ostracods of the family Entocytheridae are obligate ectosymbionts of other crustaceans, including crayfishes, isopods, amphipods, and a species of freshwater crab. Entocytheridae, with five subfamilies, 35 genera, and 213 currently accepted species, represents one the most diverse groups of extant freshwater ostracods. Here, we present the results of an extensive literature review, documenting the often complex historical taxonomic activity and resulting classification of Entocytheridae. This overview highlights inconsistencies, errors, and additional sources of confusion that have been inadvertently introduced into the literature, a number of which have remained uncorrected for decades. Also provided is a comprehensive checklist of taxonomic nomenclature and a list of currently accepted names in Entocytheridae.